SEIGNIORAGE DALAM PERSPEKTIF MONETER ISLAM - HASAN, ASYARI (Faculty of Shariah of State Institute for Islamic Studies Batusangkar, Indonesia, 2015)
Seigniorage refers to any profits resulting from issuing particular currency. Seigniorage is basically profits made by a country from the initial use of fiat money. As the issuer of a currency, a country gets profits resulting from the differences value of production cost and nominal value stated on the money. On the other hand, to earn some money, citizens need to works hard and spend time. Consequently, there seems to be a gap between what the citizens get and the profits the government makes. Dealing with this phenomena, Islam demands balance and fairness in any forms of economic phenomena, including the production of currency.Kata kunci: seigniorage, token, legal tender, float exchange rate, fiat, intrinsik, ekstrinsik, resources